2015
DOI: 10.1016/j.juro.2015.07.081
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Outcomes Following Robot-Assisted Laparoscopic Nephroureterectomy with Bladder Cuff Excision for Upper Tract Urothelial Carcinoma

Abstract: Our reported data on oncologic outcomes following robot-assisted laparoscopic nephroureterectomy with bladder cuff excision for upper tract urothelial carcinoma demonstrate satisfactory oncologic control at intermediate term followup. Long-term outcomes are required to assess true efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…A similar use can be supposed for flakelets and bladelets produced by bipolar technique, as hinted at by some ethnographic, archaeological and experimental instances (White and White, 1968;Chauchat et al, 1985;Shott, 1989;Crovetto et al, 1994;Le Brun-Ricalens, 2006;Riel-Salvatore, 2009;de la Peña et al, 2018;Moroni et al, 2018a), and underpinned by the very preliminary results from the use-wear studies carried out on a few elements from Cavallo, Castelcivita and Uluzzo C. Lithic technology is a proxy for human behaviour as well. Bipolar technique has been commonly recognised as an "expedient" production system used to save time and energy during possible "crisis" conditions (Callahan, 1987;Shott, 1989;Jeske, 1992;Hiscock, 1996;Diez-Martín et al, 2011;Mackay and Marwick, 2011;Eren et al, 2013;Morgan et al, 2015). In the archaic Uluzzian, bipolar knapping is associated with the extensive use of a very singular technique in making tools -mostly end-scrapers and side-scrapersby directly retouching thin slabs without any previous debitage.…”
Section: Discussionmentioning
confidence: 99%
“…A similar use can be supposed for flakelets and bladelets produced by bipolar technique, as hinted at by some ethnographic, archaeological and experimental instances (White and White, 1968;Chauchat et al, 1985;Shott, 1989;Crovetto et al, 1994;Le Brun-Ricalens, 2006;Riel-Salvatore, 2009;de la Peña et al, 2018;Moroni et al, 2018a), and underpinned by the very preliminary results from the use-wear studies carried out on a few elements from Cavallo, Castelcivita and Uluzzo C. Lithic technology is a proxy for human behaviour as well. Bipolar technique has been commonly recognised as an "expedient" production system used to save time and energy during possible "crisis" conditions (Callahan, 1987;Shott, 1989;Jeske, 1992;Hiscock, 1996;Diez-Martín et al, 2011;Mackay and Marwick, 2011;Eren et al, 2013;Morgan et al, 2015). In the archaic Uluzzian, bipolar knapping is associated with the extensive use of a very singular technique in making tools -mostly end-scrapers and side-scrapersby directly retouching thin slabs without any previous debitage.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the robotic platform, these limitations were overcome, and multiple studies have shown the oncologic efficacy of the robotic approach. 3,4 Since first approved in 2000 by the Food and Drug Administration, the da Vinci robot (Intuitive Surgical, Inc., Sunnyvale, CA) has undergone numerous changes and advances. In 2014, the fourth generation platform, daVinci Xi, was introduced with the goals of easier docking, wider range of motion, and multiquadrant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on early postoperative convalescence and a better cosmetic outcome, laparoscopic radical nephroureterectomy (LRNU) has now emerged as an alternative treatment method to open radical nephroureterectomy (ORNU) for patients with urothelial carcinoma (UC) of the upper urinary tract (UUT). A robot-assisted procedure has also been introduced, with acceptable short-term outcomes ( 1 , 2 ). So far, a number of studies have compared oncological outcomes, including disease recurrence and survival, between LRNU and ORNU.…”
Section: Introductionmentioning
confidence: 99%